New Exact Solutions of the New Hamiltonian Amplitude Equation and Fokas-Lenells Equation - Demiray, Seyma Tuluce; Bulut, Hasan (Mdpi, 2015)
In this paper, exact solutions of the new Hamiltonian amplitude equation and Fokas-Lenells equation are successfully obtained. The extended trial equation method (ETEM) and generalized Kudryashov method (GKM) are applied to find several exact solutions of the new Hamiltonian amplitude equation and Fokas-Lenells equation. Primarily, we seek some exact solutions of the new Hamiltonian amplitude equation and Fokas-Lenells equation by using ETEM. Then, we research dark soliton solutions of the new Hamiltonian amplitude equation and Fokas-Lenells equation by using GKM. Lastly, according to the values of some parameters, we draw two and three dimensional graphics of imaginary and real values of certain solutions found by utilizing both methods.
Keywords: new Hamiltonian amplitude equation; Fokas-Lenells equation; extended trial equation method; generalized Kudryashov method; rational function solution; travelling wave solution; hyperbolic function solution; dark soliton solution